The association between perceptual-cognitive processes and response time in decision making in young soccer players - da Silva Leite Cardoso, F.; Afonso, J.; Roca, A.; Teoldo, I. (Journal of Sports Sciences, 2021)
In soccer, it is relevant to understand the roles of Systems 1 (intuitive) and 2 (deliberative) in perceptual-cognitive processes and how they influence response time when making decisions. The aim of this study was to analyse how response time in decision making managed by Systems 1 and 2 is associated to the perceptual-cognitive processes of young soccer players. Ninety young soccer players participated. Perceptual-cognitive processes were assessed through visual search strategies, cognitive effort, and verbal reports. Participants wore a mobile-eye tracking system while viewing 11-a-side match play video-based soccer simulations. Response time in decision making was used to create two sub-groups: faster and slower decision-makers. Results indicated that players with faster response time in decision making employed more fixations of shorter duration, displayed less cognitive effort, as well as a greater number of thought processes associated with planning. These results reinforce that there are differences in the way of using the perceptive-cognitive processes from the priority system in the decision-making process. It is concluded that faster decision making, managed by System 1, implies greater ability to employ visual search strategies and to process information, thus enabling increased cognitive efficiency.